ANALISIS PENGARUH PROFESIONALISM, JOB EXPERIENCE, DAN JOB AUTONOMY TERHADAP JOB PERFORMANCE (Studi pada Advokat di Purwokerto) - Herwiek Diyah Lestari; Ady Achadi; Nirmala; Mayla Survey Andini (FEB UNWIKU PURWOKERTO, 2020)
The purpose this study is to analyze Effect of Professionalism, Job experience, and Job Autonomy on Job Performance Advocate in Purwokerto.This research was conducted at Advocate in Purwokerto. The number of samples used by 52 respondents, and the sample collection technique using a purposive sampling method. To determine the sample size using methods developed by Isaac and Michael, as well as Krejcie and Morgan.The independent variables in this study Profesionalism, Job Experience and Job Autonomy with the dependent variable is Job Performance. The analytical tool used path analysis. The results of the analysis using path analysis, found that the variable Profesionalism, and Job Experience positive effect on Job Performance. As for the variables Job Autonomy negatively affect job performance. Results of analysis using t-test can be known Profesionalism, and Job Experience significant effect on Job Performance. As for Job Autonomy no significant effect on job performance. Professionalism has the most impact on Job Performance. To improve Profesionalism an Advocate can be reached by building awareness of the profession through devotion to the profession (dedication), social obligations (social obligation) have good relations with other professions and communities, Independence (autonomy demands) are able to make decisions without pressure from others, and confidence in the rule itself / profession (belief in self-regulation)